Systemic risk and Efficiency analysis of the banking sector: A comparative study of Indian Public and Private Banks - Chhabra, Khushdil; Soni , Pooja; Gill, Suveera (Gyan Management Journal, 2023)
The academics, policymakers and regulators have shown significant curiosity in the study of systemic risk. Intra-country systemic risk has been studied in context of developed economies, but in the context of developing economies it seems to be rare. This research paper’s objective is to present an innovative presentation of the complex interplay between efficiency and systemic risk in Indian banking sector- public and private banks. Due to disagreement among the scholars regarding the relationship between these two factors, we tried to investigate this issue by collecting data from banks listed on the Nifty PSU Bank Index and Nifty Private Bank Index over the period from 2003-04 to 2018-19. The fundamental connection between efficiency and systemic risk has been checked threw granger causality. The results indicate that efficiency and systemic risk are significantly and negatively related, and the relationship is bi-directional for private banks and uni-directional for public banks. Both scholars and regulators could benefit from this article findings.